Moxibustion on Governor Vessel Acupoints Improves the Cognitive Function and TCM Symptoms in Patients with Post-stroke Mild Cognitive Impairment Due to Deficiency of Kidney Essence - Yan WANG, Yanjie BAI, Ming ZHANG, Xiaoxiao LI, Yongchuang ZHANG (Zhongguo quanke yixue, 2022)
Background Post-stroke mild cognitive impairment (PSMCI) is a common complication after stroke, which negatively affects patients' full recovery from stroke and imposes financial and emotional pressure on their families. Objective To observe the clinical efficacy of moxibustion on Governor vessel on the cognitive function and TCM syndromes in PSMCI due to deficiency of kidney essence. Methods Eligible patients with PSMCI (n=60) who were treated in Rehabilitation Center, the First Affiliated Hospital of Henan University of CM from July 2020 to July 2021 were selected, and evenly randomized to a control group (routine basic treatment plus routine cognitive rehabilitation training) and a moxibustion group 〔routine basic treatment plus routine cognitive rehabilitation training and moxibustion on the Governor vessel acupoints (once daily, five times per week) 〕, received four consecutive weeks of treatment. The Mini-Mental State Examination (MMSE) , and Montreal Cognitive Assessment (MoCA) were used to assess the cognitive function. Symptoms of kidney essence deficiency was assessed by the Scale for the Differentiation of Syndromes of Vascular Dementia (SDSVD) . And quality of life was measured by the Specifications for Stroke-Quality of Life (SS-QOL) . The overall clinical efficacy and safety of the two treatments were evaluated. Results Pre- and post-treatment comparisons of scores of MMSE and MoCA, SDSVD, and SS-QOL revealed that moxibustion group patients group had greater improvements in cognitive function, symptoms of kidney essence deficiency, and quality of life than control group patients (P<0.05) . Moreover, moxibustion group patients had better clinical outcomes (P<0.05) . The safety of treatment showed no significant intergroup differences (P>0.05) . Conclusion Moxibustion of the Governor vessel helps to better improve the cognitive function and TCM symptoms of PSMCI patients due to deficiency of kidney essence with good clinical efficacy and safety.